2016
DOI: 10.1002/chem.201604649
|View full text |Cite
|
Sign up to set email alerts
|

Twisted Polycyclic Arenes from Tetranaphthyldiphenylbenzenes by Controlling the Scholl Reaction with Substituents

Abstract: Herein, we report two new types of twisted polycyclic arenes (2 a, b and 3 a, b) with constitutionally isomeric π-backbones, which are synthesized by controlling the Scholl reaction of 1,2,4,5-tetra(naphth-2-yl)-3,6-diphenylbenzene (1) with properly positioned electron-donating substituents. With a polycyclic backbone containing two [5]helicene and four [4]helicene moieties, 2 a and b are new members of multiple helicenes with interesting stereochemistries. The as-synthesized 2 a and b are the twisted isomers,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(48 citation statements)
references
References 43 publications
(59 reference statements)
2
42
0
4
Order By: Relevance
“…Recently, an analogue of 202 with two [6]helicene parts has also been described by using oxidative coupling in the final step . Moreover, Miao and co‐workers described a similar double helicene with a PAH skeleton regioisomeric to 202 …”
Section: Intramolecular Oxidative Aromatic Couplingmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, an analogue of 202 with two [6]helicene parts has also been described by using oxidative coupling in the final step . Moreover, Miao and co‐workers described a similar double helicene with a PAH skeleton regioisomeric to 202 …”
Section: Intramolecular Oxidative Aromatic Couplingmentioning
confidence: 99%
“…[230] Moreover,M iao and co-workers described as imilar double helicene with aP AH skeleton regioisomeric to 202. [231] Itami and co-workers synthesized ad ouble [6]helicene 203 by the reaction of tetra(biphenyl)-substituted naphthalene with DDQ/TfOH in dichloroethane ( Figure 17). [232] Similar to 202,t he product was also obtained as am ixture of three diastereoisomers.A na nalogous reaction of at hiophene-based precursor with MoCl 5 in dichloromethane over 4 molecular sieves afforded the not fully cyclized tetrahelicene 204 instead of the expected double helicene.…”
Section: Curved Twisted and Strained Structuresmentioning
confidence: 99%
“…[2] Im Unterschied zu einzelsträngigen Helices,f ürd ie es zahlreiche Literaturbeispiele gibt, [3] sind Helicene mit mehreren Helicenunterstrukturen weitestgehend unerforscht, obwohl sie interessante Eigenschaften wie erhçhte molekulare Verzerrung und mehrdimensionale intermolekulare Wechselwirkungen im Festkçrper haben. [5] Im letzten Jahr gelang Itami et al die Herstellung eines neuartigen Doppel- [6]Carbohelicens mit erweitertem p-System. [4d] Doppelhelicene,d ie aus zwei kondensierten helikalen Strukturen bestehen, sind der prominenteste Fall von Multihelicenen, und es wurden in den letzten Jahren erkennbare Fortschritte in diesem Gebiet gemacht.…”
Section: Ortho-anellierte Arene Sind Eine Klasse Helixfçrmigerunclassified
“…[4] Die Pionierarbeit geht auf PØrez et al zurück, die Hexabenzotriphenylen herstellen konnten. [5b] Hatakeyama et al beschrieben die Synthese eines OBO-anellierten Doppel- [5]Heterohelicens,d as im dreidimensionalen Raum eine p-p-Wechselwirkung im Festkçrper aufwies. [5] Im letzten Jahr gelang Itami et al die Herstellung eines neuartigen Doppel- [6]Carbohelicens mit erweitertem p-System.…”
Section: Ortho-anellierte Arene Sind Eine Klasse Helixfçrmigerunclassified
“…From af undamental point of view,t hose systems are interesting where for example,acompeting situation exists and both five-or six-membered rings are possible,t ounderstand why in some cases the system tends to six-membered rings and in the other to the five-membered ones. [5j,6b, 10] With the exception of an intramolecular oxylation during Scholl-type CÀCbond formation of apicene, [11] and afourfold mesyloxylation [12] no other such selective oxylations during Scholl-type cyclization was observed, although it has been reported that it occurred instead of cyclization as acompeting reaction. There are few examples on larger PA Hs,w here selective post-functionalizing has been reported.…”
mentioning
confidence: 96%